Talent Mapping in Fun English for Differentiated Learning at Islamic Schools - Tiara Nadilah; Saipul Annur; Baldi Anggara (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2026)
This study examines how structured talent mapping can support the implementation of differentiated English learning through Fun English activities at the elementary school level. Although Fun English programs are widely used to create engaging learning environments, their implementation is often conducted uniformly and does not fully consider students’ diverse talents and learning characteristics. This study aims to identify teachers’ strategies in recognizing students’ potential talents through Fun English activities and to analyze how such identification contributes to improving the quality of English learning. The study employed a qualitative approach with a case study design conducted in an Islamic elementary school. Data were collected through classroom observations, in-depth interviews with the school principal and English teacher, and analysis of instructional documents. The findings reveal that talent identification is generally carried out informally and is not systematically documented, resulting in relatively homogeneous learning activities. Consequently, students’ participation and confidence in using English develop unevenly. These findings highlight the importance of integrating structured talent mapping to promote more differentiated, inclusive, and student-centered English learning in Islamic elementary education.